2020
DOI: 10.2320/matertrans.mt-mn2019012
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Effect on Nitrogenation of Sm<sub>2</sub>Fe<sub>17</sub>

Abstract: Nitrogenation of Sm 2 Fe 17 powder was performed under a zero field and a magnetic field of 5 T at 623, 673 and 743 K to clarify the magnetic field effect on nitrogenation. Applying a magnetic field of 5 T induced nitrogenation compared with zero-field nitrogenation, and almost fully nitride Sm 2 Fe 17 N 2.9 was obtained at 743 K. Mössbauer spectroscopy results suggested that a 5-T magnetic field promoted the phase transformation to the fully-nitride Sm 2 Fe 17 N 3 phase. The magnetic field effect was discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In the fourth paper, 171) the magnetoresistance measurements of exchange-biased spin valve device under high pressure to aim to promote the study of high-pressure studies on spintronic devices with nano structures. The fifth paper 172) reports the magnetic field effect on nitrogenation of Sm 2 Fe 17 under a zero field and a magnetic field of 5 T changing the temperature, i.e., at 623, 673 and 743 K, which revealed that application of magnetic field enhances nitrogenation. The sixth paper 173) investigates the spin reorientation and Currie temperature of Mn 2¹x Fe x Sb 1¹y Sn y .…”
Section: Magnetic Materialsmentioning
confidence: 99%
“…In the fourth paper, 171) the magnetoresistance measurements of exchange-biased spin valve device under high pressure to aim to promote the study of high-pressure studies on spintronic devices with nano structures. The fifth paper 172) reports the magnetic field effect on nitrogenation of Sm 2 Fe 17 under a zero field and a magnetic field of 5 T changing the temperature, i.e., at 623, 673 and 743 K, which revealed that application of magnetic field enhances nitrogenation. The sixth paper 173) investigates the spin reorientation and Currie temperature of Mn 2¹x Fe x Sb 1¹y Sn y .…”
Section: Magnetic Materialsmentioning
confidence: 99%